Intraoperative radiotherapy in early breast cancer. Issue 6 (17th March 2015) - Esposito, E.; Anninga, B.; Harris, S.; Capasso, I.; D'Aiuto, M.; Rinaldo, M.; Douek, M.
<x xml:space="preserve">Abstract</x> Background Intraoperative radiotherapy (IORT) constitutes a paradigm shift from the conventional 3–5 weeks of whole‐breast external beam radiotherapy (EBRT). IORT enables delivery of radiation at the time of excision of the breast tumour, targeting the area at highest risk of recurrence, while minimizing excessive radiation exposure to healthy breast tissue. The rationale for IORT is based on the observation that over 90 per cent of local recurrences after breast‐conserving surgery occur at or near the original operation site. Methods This article reviews trials of IORT delivered with different techniques and devices. Results IORT is a very attractive option for delivering radiotherapy, reducing the traditional fractionated treatment to a single fraction administered at the time of surgery. IORT has been shown to be associated with reduced toxicity and has several potential benefits over EBRT. Only two randomized clinical trials have been published to date. The TARGIT‐A and ELIOT trials have demonstrated that IORT is associated with a low rate of local recurrence, although higher than that after EBRT (TARGIT‐A: 3·3 versus 1·3 per cent respectively, P = 0·042; ELIOT: 4·4 versus 0·4 per cent, P < 0·001). However, the local recurrence rate for IORT fell within the predefined 2·5 per cent non‐inferiority margin in TARGIT‐A, and the 7·5 per cent equivalence margin in ELIOT. Conclusion Longer follow‐up data from existing trials, optimization of patient criteria and cost‐effectiveness analyses are needed. Based on the current evidence, IORT can be offered as an alternative to EBRT to selected patients within agreed protocols, and outcomes should be monitored within national registries.